Customer trust in online shopping at Taman Lembah Bujang / Nusratina Khalid and Nur Auni Afiqah Zaidi - Khalid, Nusratina; Zaidi, Nur Auni Afiqah (2019)
This chapter focuses on the background of these studies, which is customer trust in online shopping. It introduces the overall concept of customer trust and followed by problem statement, research question, research objectives, scope of study, significance of the study, and the definition of terms and concepts that is use in this study